2020
DOI: 10.1001/jamacardio.2020.1096
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Involvement in a Patient With Coronavirus Disease 2019 (COVID-19)

Abstract: IMPORTANCE Virus infection has been widely described as one of the most common causes of myocarditis. However, less is known about the cardiac involvement as a complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. OBJECTIVE To describe the presentation of acute myocardial inflammation in a patient with coronavirus disease 2019 (COVID-19) who recovered from the influenzalike syndrome and developed fatigue and signs and symptoms of heart failure a week after upper respiratory tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
1,714
6
132

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,664 publications
(1,892 citation statements)
references
References 15 publications
40
1,714
6
132
Order By: Relevance
“…Heart failure and myocardial dysfunction have been described in COVID-19 (53,55,58,60,63 The general pattern of fatalities across the age groups appears to be consistent throughout the world. In general, greater age is associated with greater risk of severe disease as well as death.…”
Section: Heart Failure Cardiogenic Shock and Myocarditismentioning
confidence: 84%
See 2 more Smart Citations
“…Heart failure and myocardial dysfunction have been described in COVID-19 (53,55,58,60,63 The general pattern of fatalities across the age groups appears to be consistent throughout the world. In general, greater age is associated with greater risk of severe disease as well as death.…”
Section: Heart Failure Cardiogenic Shock and Myocarditismentioning
confidence: 84%
“…Based on serial assessment of troponin, researchers in China reported that the median time to the development of acute cardiac injury was 15 days (IQR 10 -17) after illness onset, occurring after the development of ARDS (53). Of note, early cardiac injury has been reported, even in the absence of respiratory symptoms (60). In a case series by Shi et al, the mortality rate for those hospitalized with subsequent evidence of cardiac injury was significantly higher than those without cardiac injury (51.2% vs 4.5%, p<0.001) and, along with ARDS, was an independent predictor of death (56).…”
Section: Cardiac Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 can also directly result in a number of cardiovascular complications, including fulminant myocarditis, myocardial injury, heart failure, and arrhythmia (1,3,4). There have been a number of published case reports of clinically suspected myocarditis with markedly elevated troponin levels, ST-segment elevations on electrocardiogram without obstructive coronary disease in the presence of severely decreased left ventricular systolic function and shock (5), with cardiac magnetic resonance imaging evidence of diffuse myocardial edema and gadolinium enhancement (6). However, in another isolated autopsy report from a patient who suffered from SARS-CoV-2related pneumonia and cardiac arrest, no obvious histological changes in the myocardium were observed with the exception of few interstitial mononuclear inflammatory infiltrates (7).…”
Section: Covid-19 and Cardiovascular Complicationsmentioning
confidence: 99%
“…. Des altérations cardiaques structurelles ou inflammatoires ont également été rapportées [2,3] avec jusqu'à 23 % d'insuffisance cardiaque dans certaines séries hospitalières [4]. De nombreuses thérapeutiques sont en cours d'évaluation clinique (au 8 avril 2020), certaines pouvant éventuellement favoriser l'allongement de l'intervalle QT (chloroquine, hydroxychloroquine, azithromycine, lopinavir/ritonavir et d'autres).…”
unclassified